Energy efficient model for biogas production in farm scale - Huopana, Tuomas (2011)
Energy efficient solutions for six farm biogas production was found by calculating mass and energy balance in different scenarios. Raw materials in biogas production were cow manure and grass silage that were produced in these farms. There were calculated mass and energy balances on average for one year biogas prouduction that consisted of grass silage production, raw material transportation and biogas production in the biogas plant. In addition, direct greenhouse gases from biogas production were estimated. The direct mass and energy flows were calculated. It turned out that one input energy unit can produce 5.0 to 5.5 energy units as heat and electricity. Biogas reactor consumed heat from 42 to 66 % of the produced electricity. The electricity consumption in the biogas plant was from 12 to 18 % of the produced electricity. Energy consumption in the raw material transportation was from 7 to 14 % of the produced electricity. Energy consumption in the grass silage production was from 11 to 16 % of the produced electricity. In the electricity production the heat is also produced that should be utilized to keep the total energy balance positive. If the heat utilizer would not considered, the direct carbon dioxide emissions and the energy consumption in transportation could be decreased by one third. The energy consumption in the grass silage production consisted of an energy consumption in the field and a transportation energy consumption between farms and their field blocks. It turned out that the transportation energy consumption can be even more than half of the energy consumption in the field. By replacing mineral fertilizers with digestate, it could be possible to half the need of mineral fertilizers from present situation.